2019
DOI: 10.1108/bfj-04-2019-0294
|View full text |Cite
|
Sign up to set email alerts
|

Does the denomination taste better than the wine?

Abstract: Purpose The purpose of this paper is twofold: first, to investigate whether consumer preferences differ for wines with diverse price points and second, to analyze the effect of denominations of origin information on preferences. Design/methodology/approach In, total 150 regular wine buyers expressed their willingness-to-pay (WTP) for 12 red wines of 3 denominations (Chianti Classico DOCG, Morellino di Scansano DOCG and Toscana IGT) with three price points (basic=€5, medium=€10 and high=€20) in an incentive-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Swahn et al (2012), indicate that consumer choice of red apple was affected by the sensory description label. Vecchio et al (2019) investigate whether consumer preferences differ for wines with diverse prices. The authors analyzed the effect of denomination of origin information on preference and found it increases WTP for wines of all prices for all denominations.…”
Section: Introductionmentioning
confidence: 99%
“…Swahn et al (2012), indicate that consumer choice of red apple was affected by the sensory description label. Vecchio et al (2019) investigate whether consumer preferences differ for wines with diverse prices. The authors analyzed the effect of denomination of origin information on preference and found it increases WTP for wines of all prices for all denominations.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, Wine preference and selection studies extrinsic features are even stronger than intrinsic attributes in influencing consumers' preferences. For instance, Vecchio et al (2019b) studied the role of the wine price and the denomination of origin on influencing the consumer preferences. On the one hand, they documented that in a blind tasting session, price did not determine the consumer preferences.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, extrinsic features are even stronger than intrinsic attributes in influencing consumers' preferences. For instance, Vecchio et al. (2019b) studied the role of the wine price and the denomination of origin on influencing the consumer preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Participants expressed their general liking for Sangiovese wines ( a priori liking M = 4.4). Individual wine involvement was measured ( M = 5.1) together with wine knowledge ( M = 4) (for a detailed overview of the dataset see [ 30 ]). The final sample was composed of 62% male, 42% completed secondary school, and 36% graduated from university; the average age was 41.6 years old ( S.D .…”
Section: Methodsmentioning
confidence: 99%
“…A trained panel composed of five females (aged 35-50 years) and eight males (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) participated in the wine evaluation sessions. The thirteen assessors were previously trained for the evaluation of astringency and mouthfeel sensations, as described in Rinaldi and Moio [16].…”
Section: Wine Evaluation By Trained Assessorsmentioning
confidence: 99%